(untitled) (Journal of Applied Oral Science, 2012)
Direct composite resin restorations have become a viable alternative for patients that require anterior restorative procedures to be integrated to the other teeth that compose the smile, especially for presenting satisfactory esthetic results and minimum wear of the dental structure. Technological evolution along with a better understanding of the behavior of dental tissues to light incidence has allowed the development of new composite resins with better mechanical and optical properties, making possible a more artistic approach for anterior restorations. The combination of the increasing demand of patients for esthetics and the capacity to preserve the dental structure resulted in the development of different incremental techniques for restoring fractured anterior teeth in a natural way. In order to achieve esthetic excellence, dentists should understand and apply artistic and scientific principles when choosing color of restorative materials, as well as during the insertion of the composite resin. The discussion of these strategies will be divided into two papers. In this paper, the criteria for color and material selection to obtain a natural reproduction of the lost dental structures and an imperceptible restoration will be addressed.